HUBUNGAN ANTARA CITRA TUBUH DENGAN KECEMASAN BERBICARA DI DEPAN UMUM PADA MAHASISWA TAHUN PERTAMA FAKULTAS ILMU KOMUNIKASI UNIVERSITAS PADJADJARAN - RAHMADANI, TIKA AMELIA; Sawitri, Dian Ratna (Empati, 2017)
Communication Science of Faculty is a faculty that involves a lot of public speaking activities in the course. Therefore, students in Faculty of Communication Science are required to have good communication value. This research aims to determine the relationship between body image and public speaking anxiety in student of Communication Science Faculty of Padjadjaran University. The sample is 221 student of Communication Science Faculty of Padjadjaran University, consisted of Â 72 men and 149 women which obtained using convenience sampling technique. Data obtained using Body Image Scale (33 aitem; Î±= .91) and Public Speaking Anxiety Scale (31 item, dengan Î±= .94) which already tested to 45 students. The result of simple regression analysis shows a negative and significant relationship between body image and public speaking anxiety. Body image gives effective contribution of 20.25% toward public speaking anxiety, while the rest of 79.75% is determined by other factors.Â